Розвиток генеруючих потужностей у Молдавській енергетичній системі на базі використання парогазових установок - Bicova E.V.; Kiorsac M.V.; Postoati V.M. (General Energy Institute of the National Academy of Sciences of Ukraine, 2003)
In clause the expediency of additional input of new capacities for the combined production of electrical and thermal energy in a number of cities and occupied items of Republic of Moldova is proved by construction modern steam gas plants (SGP). It allows to increase efficiency of using the imported natural gas roughly on 20%, provides necessary balance of electrical capacity and decrease of losses in networks. The results of accounts are given. For 40 cities and occupied items the choice of capacity SGP by summary electrical capacity - 1140 MW and thermal - 860 Gkal/h is carried out.